Perancangan Terminal Penumpang Angkutan Jalan Bonawang di Kota Kotamobagu dengan Pendekatan Arsitektur High-Tech - Muhammad Fahrezi Umbola; Niniek Pratiwi; Muh. Rizal Mahanggi (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
Public transportation terminals play a crucial role in supporting the land transportation system, particularly in terms of user mobility, inter-regional connectivity, and the provision of public services. Terminal Bonawang, located in Kotamobagu City, is a Type B terminal that recorded a passenger growth of approximately 6.3% between 2017 and 2021. However, this growth was not accompanied by a proportional improvement in facilities and infrastructure, necessitating a comprehensive redesign to address these challenges. This study aims to redesign Terminal Bonawang using High-Tech architectural principles to accommodate the increasing number of users while improving the quality of transportation services. The research employs a qualitative approach with data collection through literature review, field observation, and comparative studies. Findings indicate that the application of High-Tech architecture through the exploration of exposed structural elements, the use of modern materials, and the integration of information technology systems can optimally support terminal functions. This redesign is expected to serve as a solution to existing problems and become a model for a future terminal that is efficient, flexible, and user-comfort-centered.